1991
DOI: 10.1103/physreva.44.8264
|View full text |Cite
|
Sign up to set email alerts
|

Orientational order determination in liquid crystals by x-ray diffraction

Abstract: The orientational distribution function f relative to the director of elongated molecules of liquid crystals and related materials can be determined, in principle, from the intensity distribution I along equatorial arcs in the x-ray-difFraction pattern. The integral equation relating these two quantities is solved here, yielding an analytic, closed-form expression for f in terms of the measured I. Analytic expressions for several important related quantities, like the secondand fourth-order order parameters, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 25 publications
0
61
0
2
Order By: Relevance
“…At large strains the diffraction patterns looks similar to those obtained in parallel direction, with the director fully switched and the director order parameter high. Based on the azimuthal distribution of the X-ray diffraction intensity the orientational parameter has been calculated using the formula developed by Deutsch (1991).…”
Section: Resultsmentioning
confidence: 99%
“…At large strains the diffraction patterns looks similar to those obtained in parallel direction, with the director fully switched and the director order parameter high. Based on the azimuthal distribution of the X-ray diffraction intensity the orientational parameter has been calculated using the formula developed by Deutsch (1991).…”
Section: Resultsmentioning
confidence: 99%
“…At higher degree of alignment (such as, for instance, in nematic liquid crystals) the orientational distribution function significantly deviates from the measured I(β). The analytic treatment of the problem of X-ray scattering from orientationally biased medium is developed by Deutsch [29], mainly in the context of nematic liquid crystals. Instead of using the full theory, we have derived an interpolating analytical approximation to the complete results of [29].…”
Section: X-ray Data Analysismentioning
confidence: 99%
“…The analytic treatment of the problem of X-ray scattering from orientationally biased medium is developed by Deutsch [29], mainly in the context of nematic liquid crystals. Instead of using the full theory, we have derived an interpolating analytical approximation to the complete results of [29]. With that, the orientational order parameter is given by…”
Section: X-ray Data Analysismentioning
confidence: 99%
“…Leadbetter [11,12] showed that the intensity distribution along the equatorial arc, thus at fixed ͉q ជ͉, can be related to the ODF of the sample. The integral equation relating these two quantities was inverted by Deutsch [13]. However, using scattering data that includes experimental errors, a numerical inversion of the integral equation is very inaccurate.…”
Section: ͑5͒mentioning
confidence: 99%
“…The inset shows the structure factor S͑q r ,0͒ for the two packing fractions lateral mean distance between neighboring molecules. An analytical inversion of this formula (12) was proposed by Deutsch [13] and reads as…”
Section: ͑10͒mentioning
confidence: 99%